2006
DOI: 10.1186/1743-8454-3-13
|View full text |Cite
|
Sign up to set email alerts
|

Choroid plexus epithelial monolayers – a cell culture model from porcine brain

Abstract: Background: The goal of the present study was to develop an in vitro choroid plexus (CP) epithelial cell culture model for studying transport of protein-mediated drug secretion from blood to cerebrospinal fluid (CSF) and vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 45 publications
1
24
1
Order By: Relevance
“…The basolateral localization of MRP1 at the CPs was confirmed by several other groups of investigators [50,51]. The localization of MRP1 suggests that MRP1 is an efflux of transport of drugs out of the CP.…”
Section: Bcsfbsupporting
confidence: 55%
See 1 more Smart Citation
“…The basolateral localization of MRP1 at the CPs was confirmed by several other groups of investigators [50,51]. The localization of MRP1 suggests that MRP1 is an efflux of transport of drugs out of the CP.…”
Section: Bcsfbsupporting
confidence: 55%
“…Similarly, mdr1a P-gp was not detected in mice by using high resolution confocal laser scanning microscopy [50]. Recently, it was demonstrated that P-gp was expressed intracellularly in primary porcine CP model [51]. The intracellular localization of P-gp raises the question about the functional role of the protein in the CP.…”
Section: Bcsfbmentioning
confidence: 97%
“…Many studies on CSF formation are carried out on cultured epithelial cells in vitro (Angelow et al, 2004; Hosoya et al, 2004; Baehr et al, 2006). As many as 8 methods have been described for measuring CSF formation in vivo (Oreskovic and Klarica, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro models of the CP have been developed to study the BCSFB function [209], including mouse [210], rat [211], porcine [212,213] and Rhesus macaque [214] primary epithelial cells and immortalized mouse and rat cells [209,211,215,216]. These models can be used to study drug delivery and clearance, as well as transporter function; for instance, the porcine model of CP epithelial cells developed by Baeh et al [213] formed a monolayer with key characteristics of the BCSFB; such as the expression of Mrp1 in the basolateral (blood-facing) membrane, similarly to its location in tissue.…”
Section: In Vitro Models Of the Bcsfb And Babmentioning
confidence: 99%